Replicative fitness recuperation of a recombinant murine norovirus – in vitro reciprocity of genetic shift and drift. (3rd May 2020) - Ludwig-Begall, Louisa F.; Lu, Jia; Hosmillo, Myra; de Oliveira-Filho, Edmilson F.; Mathijs, Elisabeth; Goodfellow, Ian; Mauroy, Axel; Thiry, Etienne
Abstract : Noroviruses are recognized as the major cause of non-bacterial gastroenteritis in humans. Molecular mechanisms driving norovirus evolution are the accumulation of point mutations and recombination. Recombination can create considerable changes in a viral genome, potentially eliciting a fitness cost, which must be compensated via the adaptive capacity of a recombinant virus. We previously described replicative fitness reduction of the first in vitro generated WU20-CW1 recombinant murine norovirus, RecMNV. In this follow-up study, RecMNV's capability of replicative fitness recuperation and genetic characteristics of RecMNV progenies at early and late stages of an adaptation experiment were evaluated. Replicative fitness regain of the recombinant was demonstrated via growth kinetics and plaque size differences between viral progenies prior to and post serial in vitro passaging. Point mutations at consensus and sub-consensus population levels of early and late viral progenies were characterized via next-generation sequencing and putatively associated to fitness changes. To investigate the effect of genomic changes separately and in combination in the context of a lab-generated inter-MNV infectious virus, mutations were introduced into a recombinant WU20-CW1 cDNA for subsequent DNA-based reverse genetics recovery. We thus associated fitness loss of RecMNV to a C7245T mutation and functional VP2 (ORF3) truncation and demonstrated individual and cumulative compensatory effects of one synonymous OFR2 and two non-synonymous ORF1 consensus-level mutations acquired during successive rounds of in vitro replication. Our data provide evidence of viral adaptation in a controlled environment via genetic drift after genetic shift induced a fitness cost of an infectious recombinant norovirus.